The Effectiveness of Using the Educational Game Wordwall on Students’ Learning Outcomes in Fraction Material for Fifth Grade at Ketol Public Elementary School 6 - Wati, Lina; Maisura, Maisura; Santi, Yulia (FKIP - Universitas Riau, 2025)
This study examined the effectiveness of the educational game Wordwall in improving students’ learning outcomes in fraction topics among fifth-grade students at Public Elementary School 6 Ketol, Central Aceh, Indonesia. A quantitative approach with a One-Shot Case Study design was employed, involving 37 students as participants. Data were collected through a learning achievement tes. Descriptive statistics, normality tests, and a one-sample t-test were used for data analysis. The mean post-test score was 7.13, slightly above the Minimum Mastery Criterion (KKM) of 7, although the difference was not statistically significant (p = 0.603 > 0.05). These results suggest that while Wordwall did not significantly improve test scores, it successfully enhanced motivation, discipline, and active participation in learning. Therefore, the Wordwall educational game can be considered an innovative and engaging digital tool for enhancing both cognitive and affective aspects of elementary mathematics learning.